The Role of Digital Psychological Factors in Shaping Public Acceptance of Renewable Energy Technologies: A Behavioral and Socio-Technical Perspective - Frederick Rudy Sentosa Rajagukguk (Journal of Economics, Management, Development, and Education, 2026)
This study aims to analyze the role of digital psychology factors in shaping public acceptance of renewable energy technology from a behavioral and socio-technical system perspective. In the digital era, the technology adoption process is not only determined by technical and economic aspects, but also influenced by exposure to digital information, social media, and online interactions that shape people's perceptions, attitudes, and behavioral intentions. This study uses a qualitative approach with a case study method to explore in depth how factors such as perceived usefulness, perceived ease of use, digital trust, perceived risk, and digital literacy influence public acceptance of renewable energy. Data were collected through in-depth interviews, digital observation, and documentation, then analyzed using an interactive analysis model through the processes of data reduction, data presentation, and drawing conclusions. The results show that digital psychology factors play a significant role in shaping public attitudes and decisions towards renewable energy. Trust in digital information and low risk perceptions increase adoption intentions, while exposure to unreliable information can hinder acceptance. In addition, social interactions in digital media strengthen social influence in the attitude formation process. These findings confirm that the transition to renewable energy is not only a technological process, but also a socio-psychological process that is heavily influenced by the digital ecosystem